2019
DOI: 10.4315/0362-028x.jfp-18-285
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effect of Camellia Seed Cake Extract on Aspergillus flavus

Abstract: Aspergillus flavus is a well-known, widespread fungus that contaminates a great number of crops used for human and animal consumption, but previous study showed that camellia seed cake was not susceptible to A. flavus. This study was designed to evaluate the antifungal effect of the active substance in camellia seed cake on the growth and production of aflatoxins of A. flavus. Eighty percent methanol extracts of camellia seed cake showed greater activity than that of 80% ethanol, ethyl acetate, and pure water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…5 Average daily feed intake, g/bird/day. 6 Feed conversion ratio, feed intake (g)/body weight gain (g).…”
Section: Growth Performancementioning
confidence: 99%
“…5 Average daily feed intake, g/bird/day. 6 Feed conversion ratio, feed intake (g)/body weight gain (g).…”
Section: Growth Performancementioning
confidence: 99%
“…These seven Chinese herbal extracts were compounded in the above ratios to give a product termed CHEC, which contains a number of active substances such as baicalein (from Scutellaria baicalensis ), eugenol (from Syzygium aromaticum ), cinnamaldehyde (from Cinnamomum cassia ), gleditsia saponins (from Gleditsia sinensis ), pogostone (from Pogostemon cablin ), acoramone (from Acorus calamu s), camellia saponins (from Camellia oleifera ). According to relevant references (Juneja & Friedman, 2007; Kai et al, 2020; Pei et al, 2020; Wang et al, 2019), these substances have strong antifungal effects and are more effective when used in combination. There have been a lack of available studies so far on the antifungal mechanism of the CHEC against post‐harvest soft rot of kiwifruit.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to explore an effective strategy to make full use of the resource to improve the economic value and health benefits of Camellia seed cake. Solvent type and polarity during the extraction process are reported to affect the nature and amounts of secondary metabolites and the biological capacity of plants (Wang et al, 2019;Tsai and Lin, 2019;Liu et al, 2019;Ngo et al, 2017). Several studies have revealed the impact of various solvents on phytochemical composition contributing to antioxidant activity and reuse them by using water and alcohol, such as methanol, ethanol and propanol, as solvents (Wang et al, 2019;Tsai and Lin, 2019;Liu et al, 2019;Ngo et al, 2017).…”
mentioning
confidence: 99%
“…Solvent type and polarity during the extraction process are reported to affect the nature and amounts of secondary metabolites and the biological capacity of plants (Wang et al, 2019;Tsai and Lin, 2019;Liu et al, 2019;Ngo et al, 2017). Several studies have revealed the impact of various solvents on phytochemical composition contributing to antioxidant activity and reuse them by using water and alcohol, such as methanol, ethanol and propanol, as solvents (Wang et al, 2019;Tsai and Lin, 2019;Liu et al, 2019;Ngo et al, 2017). Among organic solvent systems, methanol is known as an efficient solvent to extract the best, but it can cause adverse health effects and cannot be directly used (Wang et al, 2019;Tsai and Lin, 2019;Liu et al, 2019;Ngo et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation